Power Flow Features and Balancing in MTDC Integrated Offshore Wind Farms. Issue 10 (15th June 2017) - Li, Yujun; Xu, Zhao; Meng, Ke; Wong, Kit Po
Abstract: This paper proposes a novel control strategy for converter stations of multi-terminal DC (MTDC) grid system. It optimizes the offshore wind farms power generation dispatched to the separate onshore AC systems while minimizing their impacts on AC grids. Based on the MTDC power flow analysis, the minimal control dimensions of MTDC converters are firstly proposed. The impact of DC resistances on power dispatching among MTDC grid is then fully discussed by analyzing the structure of inverse Jacobian matrix of MTDC grid power flow equation and the power dispatch law for each onshore AC grid is deduced subsequently. Finally, an optimization strategy that seeks to re-dispatch the power to each onshore converter according to the system inertia of connected AC grid is proposed. Case study using a typical five-terminal MTDC system shows that the proposed strategy can effectively mitigate wind power fluctuations by approximately equalizing the induced disturbances to the system frequency of each AC grid.